Perspectives of ESCAPE-pain programme for older people with knee osteoarthritis in the community setting - Che Hasan, Muhammad Kamil; Stanmore, Emma; Todd, Chris (Frontiers Media S.A., 2021)
Background: Functional limitations commonly affect patients with knee osteoarthritis (OA) which reduces quality of life. The Enabling Self-management and Coping with Arthritic Pain using Exercise (ESCAPE-pain) is an evidence-based programme identified to be suitable for adaptation for the Malaysian health care system. It is important to understand the acceptance from a sociocultural context of the ESCAPE-pain programme from the perspectives of patients with knee OA and healthcare professionals. This qualitative study aims to explore the perspectives of stakeholders to inform the adaptation of the ESCAPE-pain programme into the Malaysian health care system.